2023
DOI: 10.1158/2767-9764.crc-23-0009
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome CpG-resolution DNA Methylation Profiling of HNSCC Reveals Distinct Mechanisms of Carcinogenesis for Fine-scale HPV+ Cancer Subtypes

Tingting Qin,
Shiting Li,
Leanne E. Henry
et al.

Abstract: DNA methylation is a vital early step in carcinogenesis. Most findings of aberrant DNA methylation in head and neck squamous cell carcinomas (HNSCC) are array-based with limited coverage and resolution, and mainly explored by human papillomavirus (HPV) status, ignoring the high heterogeneity of this disease. In this study, we performed whole-genome bisulfite sequencing (WGBS) on a well-studied HNSCC cohort (n=36) and investigated the methylation changes between fine-scaled HNSCC subtypes in relation to genomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Consistently, HPV+ HNSCC tumors have been characterized as either immune strong (IMU) or highly keratinized (KRT) 13 . These subtypes have been further characterized based on mutations, CNVs, DNA methylation 18 , DNA hydroxymethylation 19 , and comprehensively reviewed in Qin et al 11 . However, previous classifications have not provided the ability to classify new tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, HPV+ HNSCC tumors have been characterized as either immune strong (IMU) or highly keratinized (KRT) 13 . These subtypes have been further characterized based on mutations, CNVs, DNA methylation 18 , DNA hydroxymethylation 19 , and comprehensively reviewed in Qin et al 11 . However, previous classifications have not provided the ability to classify new tumors.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Locati et al further discriminated KRT tumors into high and low stromal subtypes 16 , and demonstrated that IMU patients have better prognosis than either high or low stromal KRT. The subtype naming convention of IMU/KRT was adopted in the Nature review, Leemans et al 17 , and these subtypes have now been characterized using additional high-throughput technologies, including DNA methylation 18 showing stronger global hypomethylation in KRT, and DNA hydroxymethylation 19 . The IMU/KRT subtypes have also been demonstrated to significantly associate with HPV E6 isoform gene expression, with KRT tending to have higher levels of the spliced E6*I isoform compared to E6 full length 20,21 .…”
Section: Introductionmentioning
confidence: 99%